A cytomorphometric analysis of the oral mucosa in patients with type 2 diabetes mellitus - Lamichhane, RS; Boaz, K; Natrajan, S; Shrestha, M (Journal of Pathology of Nepal, 2015)
Background: Although many of the pathological conditions of oral mucosa are clinically distinguishable, most lesions require a definitive diagnosis. This article tried the use of exfoliative cytology as an alternative tool in the screening, diagnosis and follow-up of diabetes mellitus. Materials and Methods: After rinsing the mouth with normal saline, slides were prepared from buccal mucosa and dorsum of tongue and fixed in 95% ethyl alcohol. The slides were stained with Papanicolaou stain and Acridine orange. Fifty clearly defined cells in each slide were visualized under light microscope for cytomorphometric analysis of cells using Image J software and under fluorescence microscope for assessment of nuclear alterations like micronuclei, nuclear budding, binucleation, multinucleation and karyorrhexis. Results: Statistically significant increase in Nuclear area BM (p = 0.000057), Nuclear Area Tongue (p= 0.0000113), total Nuclear Area (p= 000079), Cellular Area BM (p= 0.0475), Cellular Area Tongue (p= 0.0105), Total Cellular Area (p= 0.00496), Cytoplasmic Area Tongue (p= 0.00358), Total Cytoplasmic Area (p= 0.00268) were obtained from epithelial cells in the diabetic group when compared with the control group. Also the epithelial cells from the diabetic group showed features such as nuclear budding, micronuclei, binucleation, karyorrhexis and perinuclear halo. Conclusion: The objective demonstration of cytomorphometric and nuclear alterations by the oral exfoliated cells indicate the presence of cytological changes in the oral mucosa of diabetic patients despite the apparently normal clinical appearance. Hence, cytomorphometric analysis would aid the health professional as an additional non-invasive tool for the screening and monitoring of Diabetes Mellitus.